Validation of projective mapping as potential sensory screening tool for application by the honeybush herbal tea industry. (September 2017) - Moelich, Erika Ilette; Muller, Magdalena; Joubert, Elizabeth; Næs, Tormod; Kidd, Martin
Abstract: Honeybush herbal tea is produced from the endemic South African Cyclopia species. Plant material subjected to a high-temperature oxidation step ("fermentation") forms the bulk of production. Production lags behind demand forcing tea merchants to use blends of available material to supply local and international markets. The distinct differences in the sensory profiles of the herbal tea produced from the different Cyclopia species require that special care is given to blending to ensure a consistent, high quality product. Although conventional descriptive sensory analysis (DSA) is highly effective in providing a detailed sensory profile of herbal tea infusions, industry requires a method that is more time- and cost-effective. Recent advances in sensory science have led to the development of rapid profiling methodologies. The question is whether projective mapping can successfully be used for the sensory characterisation of herbal tea infusions. Trained assessors performed global and partial projective mapping to determine the validity of this technique for the sensory characterisation of infusions of five Cyclopia species. Similar product configurations were obtained when comparing results of DSA and global and partial projective mapping. Comparison of replicate sessions showed RV coefficients > 0.8. A similarity index, based on multifactor analysis, was calculated to determine assessor repeatability. Global projective mapping, demonstrated to be a valid method for providing a broad sensory characterisation of Cyclopia species, is thus suitable as a rapid quality control method of honeybush infusions. Its application by the honeybush industry could improve the consistency of the sensory profile of blended products. Graphical abstract: Highlights: DSA and global and partial PM of different Cyclopia spp. gave similar product configurations. Comparison of replicate sessions showed RV coefficients > 0.8, indicating high repeatability between sessions Global projective mapping demonstrated to be a valid method for the broad sensory profiling of Cyclopia species. The similarity index based on MFA is a valid tool for calculating assessor repeatability.